Cholesterol Perturbation in Mice Results in p53 Degradation and Axonal Pathology through p38 MAPK and Mdm2 Activation. - Qingyu Qin; Guanghong Liao; Michel Baudry; Xiaoning Bi (PLoS ONE, 2010)
Perturbation of lipid metabolism, especially of cholesterol homeostasis, can be catastrophic to mammalian brain, as it has the highest level of cholesterol in the body. This notion is best illustrated by the severe progressive neurodegeneration in Niemann-Pick Type C (NPC) disease, one of the lysosomal storage diseases, caused by mutations in the NPC1 or NPC2 gene. In this study, we found that growth cone collapse induced by genetic or pharmacological disruption of cholesterol egress from late endosomes/lysosomes was directly related to a decrease in axonal and growth cone levels of the phosphorylated form of the tumor suppressor factor p53. Cholesterol perturbation-induced growth cone collapse and decrease in phosphorylated p53 were reduced by inhibition of p38 mitogen-activated protein kinase (MAPK) and murine double minute (Mdm2) E3 ligase. Growth cone collapse induced by genetic (npc1-/-) or pharmacological modification of cholesterol metabolism was Rho kinase (ROCK)-dependent and associated with increased RhoA protein synthesis; both processes were significantly reduced by P38 MAPK or Mdm2 inhibition. Finally, in vivo ROCK inhibition significantly increased phosphorylated p53 levels and neurofilaments in axons, and axonal bundle size in npc1-/- mice. These results indicate that NPC-related and cholesterol perturbation-induced axonal pathology is associated with an abnormal signaling pathway consisting in p38 MAPK activation leading to Mdm2-mediated p53 degradation, followed by ROCK activation. These results also suggest new targets for pharmacological treatment of NPC disease and other diseases associated with disruption of cholesterol metabolism.